Autodesk Maya 2017 basics guide - Murdock, Kelly (Mission, KS : SDC Publications, 2017)
Written by renowned author and 3D artist, Kelly L. Murdock, Autodesk Maya 2017 Basics Guide is designed to give new users a solid understanding of the fundamental skills needed to create beautiful 3D models and stunning animations with Autodesk Maya. Using clear and easy to follow instructions this book will guide you through learning all the major features of Maya. The text is complemented by video instruction. Each chapter has a corresponding video tutorial that introduces you to the topics and allows you to watch and learn how functions are performed in a way that a text alone cannot do. Autodesk Maya 2017 Basics Guide makes no assumptions about your previous experience with Autodesk Maya. It begins by helping you get comfortable with the user interface and navigating scenes before moving into modeling, texturing, lighting, animating, rendering and more. Additionally, more advanced features such as character rigging, skinning, animating with dynamics and MEL scripting are also introduced.
Includes index.
Keywords: Maya (Computer file); Computer animation; Computer graphics; Computer art; Three-dimensional display systems